Mapping the Terrain: Educational Leadership Field Experiences in K-12 Virtual Schools. (February 2014) - LaFrance, Jason A.; Beck, Dennis
Opportunities for K-12 students to choose virtual and blended learning experiences continue to grow. All 50 states including Washington, D.C., now offer some virtual experience in K-12 education. Of these, 40 states have state virtual schools or state-led online learning initiatives. In addition, federal and state support for this type of learning continues to expand. Field experiences are beginning to be available for virtual school teachers; however, little information is available on field experiences for pre-service administrators in virtual K-12 settings. This study provides a status report on the state of school administrator preparation for K-12 online and blended learning programs in the United States. This research was conducted by surveying initial certification Educational Leadership programs regarding the extent that pre-service administrators are exposed to K-12 online learning environments. Results indicate that very few Educational Leadership programs provide any administrator preparation for leading a K-12 virtual school or teachers of online courses. Important ramifications exist for Educational Leadership programs preparing educators to lead fully online and blended learning programs.